"Joining the Spots in Adults and Young Tots": A Clinicopathological Study of Henoch–Schönlein Purpura (IgA Vasculitis). (August 2017) - Kedia, Priyanka P.; Tirumalae, Rajalakshmi; Puttegowda, Divya; Antony, Meryl
Abstract : Introduction: Henoch–Schönlein Purpura (HSP; IgA vasculitis), the most common vasculitis of childhood, has a wide spectrum of clinical manifestations ranging from palpable purpura with abdominal pain and arthritis to the more morbid renal involvement. Aims and Objectives: To study and correlate the clinical presentation, laboratory values, skin and renal histopathology and immunofluoroscence findings in HSP. Material and Methods: A total of 44 cases of HSP from March 2011 to February 2014 were studied for the above features along with their clinical outcomes. Results: The mean age of the patients at presentation was 28.4 years (range 4.5–69 years) with 26.2% being children younger than 15 years. Purpura at presentation was seen in all with 77.1% cases exhibiting extracutaneous involvement. Skin biopsy revealed leukocytoclastic vasculitis in all cases, dominant IgA deposition in the papillary dermal vessels in 43 cases (97.7%), associated C3 in 10 cases (23.3%), and full-house positivity in 1 case. One case without skin immunofluorescence had renal mesangial IgA deposits. Nine cases (20.9%) with an average age of 39 years had renal symptoms and displayed varied histology from focal mesangioproliferative glomerulonephritis to crescentic. All of them had dominant mesangial IgA deposits, majority falling into International Study of Kidney Disease in Children (ISKDC) class IIIb. Peritubular capillaritis was noted in 3 cases. Two patients (4.5%) progressed to end stage renal disease, one of whom had cellular crescents at presentation. Conclusions: HSP was seen both in children and adults. Renal involvement was seen in 20.9% cases, all older than 14 years, and 66.7% with extracutaneous manifestations. The outcome in this series was favorable in 96% cases.